Growth Trend in Area, Production and Productivity of Tomato in India and Haryana (Indian Journal of Extension Education, 2024)
Tomato an economically important crop contributes significantly to horticulture production. The study was based on the secondary data regarding production, productivity and area of tomato in Haryana and India. The data was collected from various secondary resources like reports from the National Horticulture Board, Indiastat.com, horticulture statistics at a glance, agriculture statistics at a glance, and the Department of Agriculture, Cooperative and Farmers Welfare. The analysis of data was done by calculating compound annual growth rate (CAGR) and regression charts. The study concluded that tomato production in the state of Haryana and India witnessed a significant increase from 2001-02 to 2021-22. The area under tomato cultivation in Haryana and India also exhibited a positive trend. The compound annual growth rate of area, production and productivity of tomatoes in India was 3.25, 5.90 and 2.56 whereas it was 3.82, 6.63 and 2.70 per cent respectively, in Haryana. It was suggested to promote the adoption of sustainable farming practices such as integrated pest management, precision agriculture and use of high-yielding varieties among tomato growers, to enhance productivity. Better market linkages and infrastructure for value added processing should be developed to reduce post-harvest losses and ensure better returns to farmers.